2003
DOI: 10.1007/s11883-003-0033-y
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial lipemia and cardiovascular disease

Abstract: Postprandial lipemia, characterized by a rise in triglyceride-rich lipoproteins after eating, is a dynamic, nonsteady-state condition in which humans spend the majority of time. There are several lines of evidence suggesting that postprandial lipemia increases risk of atherogenesis. Clinical data show a correlation between postprandial lipoproteins and the presence/progression of coronary artery disease and carotid intimal thickness. Mechanistic studies demonstrate that triglyceride-rich lipoprotein remnants m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
102
1
12

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(119 citation statements)
references
References 74 publications
(98 reference statements)
4
102
1
12
Order By: Relevance
“…Thirty years ago, it was first proposed by Zilversmit [11] that postprandial lipemia may play a role in atherogenesis, and there is now a great deal of evidence from epidemiological, clinical and experimental studies to support the idea that postprandial hyperlipidemia is an important risk factor for atherosclerosis and the progression of cardiovascular disease [12][13][14][15]. Nakajima and colleagues have reported that the majority of sudden cardiac deaths in a Japanese cohort of patients were associated with postprandial hyperlipidemia [16] and that plasma remnant lipoprotein levels were the major pathological factor involved [17].…”
Section: Postprandial Hyperlipidemia As a Risk Factor For Atherosclermentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty years ago, it was first proposed by Zilversmit [11] that postprandial lipemia may play a role in atherogenesis, and there is now a great deal of evidence from epidemiological, clinical and experimental studies to support the idea that postprandial hyperlipidemia is an important risk factor for atherosclerosis and the progression of cardiovascular disease [12][13][14][15]. Nakajima and colleagues have reported that the majority of sudden cardiac deaths in a Japanese cohort of patients were associated with postprandial hyperlipidemia [16] and that plasma remnant lipoprotein levels were the major pathological factor involved [17].…”
Section: Postprandial Hyperlipidemia As a Risk Factor For Atherosclermentioning
confidence: 99%
“…Current evidence suggests that postprandial lipoproteins may be involved in promoting atherosclerosis both directly, via an influence on events in the vasculature, and indirectly, by causing a more atherogenic lipoprotein profile when their levels are abnormally raised [12,14,26]. Atherosclerosis is initiated by dysfunction of the vascular endothelium followed by the formation of macrophage foam cells, generated by the scavenging of lipids from plasma lipoproteins.…”
Section: Postprandial Hyperlipidemia As a Risk Factor For Atherosclermentioning
confidence: 99%
See 2 more Smart Citations
“…triglyceride-rich lipoproteins Chronic vascular inflammation is increasingly recognized as playing a central role in atherosclerosis (1,2). Recent studies have focused on repetitive injury of the vascular wall during the postprandial state (3,4), where endothelial cells lining the vascular wall are repeatedly exposed to a wide variety of lipoproteins, cytokines, and hemostatic, inflammatory, and anti-inflammatory factors. Little is known about how these postprandial factors influence lipid metabolism, and specifically the behavior of apolipoproteins in the preprandial and postprandial state.…”
Section: : 1358-1365mentioning
confidence: 99%